“THE EMPTIED AUTHORITY”: AFRICAN NEO-PENTECOSTALISM, MODERNISATION OF SACRED AUTHORITY, AND GENDERED AND SEXUALISED CONSTRUCTIONS OF VIOLENCE - C.J. Kaunda (Acta Theologica)
This article argues that African Neo-Pentecostalism has adopted indigenous notions of sacred authority through the paradigm of modernisation. Employing Rev. Timothy Omotoso’s case study on sexualisation and gendered exploitation of women and girls in South Africa, the article illustrates that the impact of modernisation is more evident in the individualised, fragmented and fundamentalised way in which Neo-Pentecostalism has resourced indigenous sacred authority. The article proposes emptied sacred authority as life-affirming and the recovery of holistic imaginations, whereby the pastor becomes a symbolic instrument of a kenotic life.